Feasibility study of emission policy for photovoltaic integrated building microgrids - Gong Xundong; Xue Mingfeng; Yang Bo; Wang Deshun; Guo Xu; Ge Yuanfei; Zhang Xiongwen (E3S Web of Conferences, 2020)
The photovoltaics (PV) based microgrids play important role in the development of green buildings. This work investigates the effects of emission policy on the PV integrated commercial and residential building microgrids. The component sizes of microgrid are determined by simulated optimal power dispatch with an optimization algorithm based on minimizing the cost of energy (COE). The COE is computed with consideration of the capital depreciation cost, fuel cost, emissions damage cost and maintenance cost. The simulation results show that the emission policy and photovoltaic subsidy have little effect on sizing the commercial microgrid system. However, the component sizing design for residential microgrid system is sensitive to the emission policy. Increasing emission taxes and photovoltaic subsidy can effectively raise the proportion of PV in the system. The most important factor of restricting PV usage in microgrids is the cost of batteries. Increasing the battery lifetime or selecting the lower cost of battery can significantly increase the installation of PV, thus rise the green building standard.